Demographic parameters of a free‐ranging deep‐diving cetacean, the long‐finned pilot whale. Issue 2 (21st October 2020) - Verborgh, Philippe; Gauffier, Pauline; Esteban, Ruth; de Stephanis, Renaud
Abstract: Demographic parameters provide baselines to estimate future population trajectories which can then be used in management decisions. The aim here was to estimate demographic parameters of long‐finned pilot whale ( Globicephala melas ) from the Strait of Gibraltar by fitting mark‐recapture models to photo‐identification data of primary and secondary marked individuals. These parameters were used to forecast the future population trajectories in a population viability analysis (PVA) given different scenarios of demographic rates. Survival rate increased with age from 0.629, 95% CI [0.409, 0.805] for calves, 0.869, 95% CI [0.758, 0.934] for juveniles, to 0.972, 95% CI [0.953, 0.983] for adults. A preliminary mean observed interval of viable calves was 4.5 years. The PVA estimated the population would persist over 100 years with a 100% probability for all scenarios except those with lower 95% CI survival values, for which the probability of extinction reached 100%. Population growth rate was negative in all scenarios except those with 95% CI upper survival values. Interbirth interval and juvenile survival were found most influential and depended on the correct identification of secondary marked (e.g., calves and juveniles) individuals on a long‐term basis. This population was found in a precarious state prior to a morbillivirus outbreak that might even more endanger its long‐term viability.